Isolation by distance and past climate resistance shaped the distribution of genealogical lineages of a neotropical lizard. Issue 1 (31st December 2022) - Camurugi, Felipe; Oliveira, Eliana F.; Lima, Guilherme S.; Marques, Ricardo; Magalhães, Felipe M.; Colli, Guarino R.; Mesquita, Daniel O.; Garda, Adrian A.
Abstract : Organisms adapted to open environments in South America have recently been used to understand the origins of the high Neotropical biodiversity. In the Caatinga, the largest continuous block of Seasonally Dry Tropical Forest in South America, phylogeographic studies have uncovered the role of historical climate changes and rivers (i.e., the São Francisco River, the largest perennial river in Caatinga), in promoting genetic differentiation and speciation of lizards and amphibians. We used mitochondrial data, demographic analyses, paleodistribution models, and landscape genetic methods to test the effects of spatial distances, historical climate fluctuations, and landscape heterogeneity on the genetic variation of the generalist lizard Tropidurus hispidus in the semi-arid Caatinga in northeastern Brazil. Four haplogroups with moderate geographical structure diverged in the Pleistocene, and exhibited high genetic diversity. Ecological niche models revealed large suitable climatic areas for T. hispidus in the past 790 thousand years, connecting the Caatinga and other regions via a narrow corridor. Part of the genetic differentiation in T. hispidus resulted from spatial distances among populations and isolation by resistance through climatic unsuitability areas in the Last Glacial Maximum (LGM), which probably reduced population connectivity and gene flow. Our findings highlight the role of the historical factors of the Caatinga, through LGM climate, and the generalist condition of species in shaping the genealogical histories of populations. Although the results are based on a single-locus approach, our study is a first step to shed light on the main drivers of the evolutionary history of T. hispidus, in a highly diverse and still poorly studied region.